Reports on using an ABB robot in Android mobile testing automation - Albuquerque, Abda; Castro, Alice; Barbosa, Heryck (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST), 2024)
There are many automation available for our daily lives that seek to improve performance and quality ensuring time reduction. For the area of telephone tests, there are many possibilities to automate mainly by dealing with sensors. The purpose of the article is to present a different way of performing the Rotation Vector Vision Crosscheck Rotation Test Case, through an ABB robot that has 7 axis and compare its performance with the existing automation proposal. An experiment of 20 executions was performed on the YuMi® robot for each of the 5 selected models. The result obtained was a rate of 85% accuracy, disregarding one of the models due to a determining factor.